The influence of infectious diseases on population genetics - Zhilan Feng; Carlos Castillo-Chavez (Mathematical Biosciences and Engineering)
Malaria is the vector-transmitted disease that causes the highestmorbidity and mortality in humans. Motivated by the known influenceof sickle-cell anemia on the morbidity and mortality ofmalaria-infected humans, we study the effect of malaria on the genetic composition of a host (human) population where sickle-cell anemia is prevalent and malaria is endemic. The host subpopulations are therefore classified according to three genotypes, $A$$A$, $AS$, and $SS$. It is known that $A$$A$ malaria-infected individuals experience higher malaria-induced mortality than $AS$ or $SS$ individuals. However, individuals carrying the $S$ gene are known to experience a higher mortality rate in a malaria-free environment than those who lack such a gene. The tradeoffs between increased fitness for some types in the presence of disease (a population level process) and reduced fitness in a disease-free environment are explored in this manuscript. We start from the published results of an earlier model and proceed to remove some model restrictions in order to better understand the impact on the natural hosts' genetics in an environment where malaria is endemic.